Oil Rents and the Structure of Public Finances in Iraq - Ali Ayed Nasir; Zainab Hadi AlKhafajy; Noof Ali Awad (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The Iraqi economy demonstrates that, despite the substantial magnitude of oil revenues, theseresources have not been effectively utilized to establish a diversified economic base capable of supportingcomprehensive development and securing the rights of current and future generations. Instead, the majority ofthese revenues are allocated to consumption patterns or to financing current expenditures, which do notcontribute to achieving sustainable development goals. This study examines the interdependence between oilrent revenues and their management, assessing the resulting improvements or declines in Iraq's financial andeconomic performance. It emphasizes the necessity of adopting prudent financial management and diversifyingincome sources to ensure long-term stability and prosperity for the country. The research problem lies in theheavy reliance of Iraq's public finances on oil rents, which exposes the economy to significant risks due tovolatile global oil prices. This dependency leads to structural weaknesses in the revenue and expenditureframework, limiting its flexibility and sustainability, and consequently hindering efforts to achievecomprehensive economic development. The results of the estimated model indicate that current public revenuesare heavily dependent on the previous year's revenues, suggesting that revenue generation is influenced byexternal factors, particularly expectations regarding fluctuations in oil prices.